An information propagation network dynamic considering multi-platform influences. (November 2022) - Yin, Fulian; Pan, Yanyan; Tang, Xinyi; Wu, Chang; Jin, Zhen; Wu, Jianhong
Abstract: To solve the traditional Susceptible–Forwarding–Immune model of information propagation ignores the social network structure and the influence of multi-platform environment, we construct a complex network SFI model that introduces environmental factors (Net-E-SFI model). This model considers the complexity of the actual social network structure and the multi-platform effect nodes in the Information dissemination environment. We perform parameter fitting using data from two real events with different levels of environmental impact, and the fitting curves are very close to the real values. Sensitivity analysis describes significant parameters related to the environment in support for decision strategies to guide public opinion.